COMPARATIVE ANALYSIS OF FEMALE CONSUMER LOYALTY LEVELS IN ONLINE AND CONVENTIONAL STORES OF COSMETIC PRODUCT TYPES - Ratna, Ikhwani; Nasrah, Hidayati (Marwah: Jurnal Perempuan, Agama dan Jender, 2024)
Progresses in innovation have made it less demanding for individuals to carry out buying and offering exercises. Since with web innovation, individuals can make buying and offering exchanges without assembly in individual. Be that as it may, buying and offering exercises carried out through online media have an impact on client devotion. This inquire about was conducted due to see how the comparison of client dependability in online stores with ordinary stores. The inquire about was conducted by conducting interviews through surveys to clients of online stores and ordinary stores by taking a test of 100 individuals. The collected information was at that point analyzed utilizing clear strategies. Based on the comes about of the ponder, it can be concluded that client devotion in customary stores is superior than client devotion in online stores. This could be seen from the comes about of surveys disseminated to respondents where customer dependability in routine stores encompasses a higher score when compared to scores at online stores.